Lala's words - Zhang, Gracey (Orchard Books, an imprint of Scholastic Inc., 2021)
Every day, no matter how hot, Lala carries a pot of water around the corner to a patch of dirt and concrete, waters the tiny weeds sprouting there, and whispers words of encouragement to her plant friends; then, on the hottest day of all, her mother insists she stay home, but Lala worries about her friends, and whispers words of love--with a magical result.